Analysis of Generation Z's Emotional Development in Broken Home Families - Aisyiarya Maharani Almadina; Dedet Erawati (Jurnal Polisci, 2026)
Background. The phenomenon of increasing divorce cases in households is increasing from year to year. There are many factors that cause divorce. From these conditions, it is not uncommon for children to experience the impact of their parents' divorce. Purpose. This analysis examines the development of Generation Z in broken home families, thus providing a deeper understanding of the importance of the role of the family in shaping the emotional development of the younger generation. Method. Using a qualitative approach, this study examines how the dynamics of a divided family are related to the development of the emotional dimension of individuals in the context. Results. By utilizing Johari's window theory to explore the self-aspects and emotional evolution of participants, this study shows that the experience of broken home families is related to Generation Z's patterns of interaction with themselves and others. Conclusion. Thus, it can be concluded that the four areas in the Johari Window model, namely open, blind, hidden, and unknown areas, have the same contribution to the emotional development of individuals.